Mortality Related to Cold Temperatures in Two Capitals of the Baltics: Tallinn and Riga - Daniel Oudin Åström (Medicina, 2019)
Background and objectives: Despite global warming, the climate in Northern Europe is generally cold, and the large number of deaths due to non-optimal temperatures is likely due to cold temperatures. The aim of the current study is to investigate the association between cold temperatures and all-cause mortality, as well as cause-specific mortality, in Tallinn and Riga in North-Eastern Europe. Materials and Methods: We used daily information on deaths from state death registries and minimum temperatures from November to March over the period 1997−2015 in Tallinn and 2009−2015 in Riga. The relationship between the daily minimum temperature and mortality was investigated using the Poisson regression, combined with a distributed lag non-linear model considering lag times of up to 21 days. Results: We found significantly higher all-cause mortality owing to cold temperatures both in Tallinn (Relative Risk (RR) = 1.28, 95% Confidence Interval (CI) 1.01−1.62) and in Riga (RR = 1.41, 95% CI 1.11−1.79). In addition, significantly increased mortality due to cold temperatures was observed in the 75+ age group (RR = 1.64, 95% CI 1.17−2.31) and in cardiovascular mortality (RR = 1.83, 95% CI 1.31−2.55) in Tallinn and in the under 75 age group in Riga (RR = 1.58, 95% CI 1.12−2.22). In this study, we found no statistically significant relationship between mortality due to respiratory or external causes and cold days. The cold-related attributable fraction (AF) was 7.4% (95% CI -3.7−17.5) in Tallinn and 8.3% (95% CI -0.5−16.3) in Riga. This indicates that a relatively large proportion of deaths in cold periods can be related to cold in North-Eastern Europe, where winters are relatively harsh.